2001
DOI: 10.1002/1521-3765(20010903)7:17<3738::aid-chem3738>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Dipolar Donor-Acceptor-Substituted Schiff Base Complexes with Large Off-Diagonal Second-Order Nonlinear Optical Tensor Components

Abstract: The synthesis, characterization, and two-dimensional second-order nonlinear optical (NLO) response of a dipolar NiII donor- acceptor Schiff base complex and the related ligand are reported. Electric-field-induced second-harmonic generation and harmonic light (hyper-Rayleigh) scattering techniques, in combination with INDO/SCI-SOS theoretical calculations, were used to investigate the vector part of the hyperpolarizability tensor and the two-dimensional character of the molecular nonlinearity, respectively. Off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(41 citation statements)
references
References 85 publications
(44 reference statements)
1
39
1
Order By: Relevance
“…The previous theoretical investigations on molecular organometallic NLO properties have mostly employed the semi‐empirical quantum chemical methods 12–15, which have been remarkably successful in the understanding of optical nonlinearities of organometallics. For example, Kanis et al 16 carried out a systemic study of the LO and NLO properties for some neutral organometallic ferrocenyl chromophores at ZINDO/sum‐over‐state (SOS) level.…”
Section: Introductionmentioning
confidence: 99%
“…The previous theoretical investigations on molecular organometallic NLO properties have mostly employed the semi‐empirical quantum chemical methods 12–15, which have been remarkably successful in the understanding of optical nonlinearities of organometallics. For example, Kanis et al 16 carried out a systemic study of the LO and NLO properties for some neutral organometallic ferrocenyl chromophores at ZINDO/sum‐over‐state (SOS) level.…”
Section: Introductionmentioning
confidence: 99%
“…1), we have designed 6 derivatives (see [2][3][4][5][6][7] in Fig. 1) in order to study how the p-conjugated bond and positions of donor (D) or acceptor (A) affect the NLO properties of DBA derivatives.…”
Section: The Geometric Structure and First Hyperpolarizabilitymentioning
confidence: 97%
“…Recently, it has been suggested that two-dimensional charge transfer (2DCT) chromophores can circumvent these problems [7,8]. 2DCT chromophores which possess multiple donor-acceptor substituents, such as ''K-shaped" [9], ''X-shaped" [10], ''Y-shaped" [11], ''U-shaped" [12], ''H-shaped" [13], have a 2D b tensor character, where the off-diagonal components become significant.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the anisotropy values were reduced to 0.51 and 0.32 in compounds Ib and IIb, respectively, due to a departure from the planarity of the pyramid amido with the electron-donating 4-ethynylbenzenamine substitution. Compounds Ib and IIb likely do not exhibit relatively significant 2D NLO properties when compared to the corresponding unsubstituted compounds Ia and IIa, while they still display typical values of 2D donor-acceptor bis(salicylaldiminato)Ni II Schiff base complexes (NiL) and the related ligands (H 2 L) [36].…”
Section: Second-order Polarizabilitiesmentioning
confidence: 99%